DEVELOPMENT OF MATERIALS BUILDING MATERIALS ENVIRONMENTAL CONSTRUCTIVE-CONSTRUCTIVE SIDE - Trisdyanto Trisdyanto (Universitas Negeri Makassar, 2013)
The purpose of this research is to construct constructive, constructive, and effective construct-based constructive spacewalk construct materials, including Student Handbook, Student Activity Sheet (LKS), and Teacher Handbook. The existence of constructivist-based learning materials is expected to create a learning situation that allows students to more construct their knowledge personally or socially. This research is a research development (Development and Development) which uses descriptive and evaluative method, and through development trials that refer to Four-D model Thiagarajan et al. (1974), with define, disign, develop, and disseminate stages. The teaching material meets the criteria of validity, meets the practical criteria for both trials, and meets the effectiveness criteria in the second trial. Thus the development of materials to get the wake-up material kosutruktivistik-based curve space valid, practical, and effective. Dissemination of teaching materials conducted on mathematics teachers in the forum MGMP Matematika SMP Kab. Pangkep and meet the criteria of effectiveness disseminate